Sportdiktatur Bewegungskulturen im nationalsozialistischen Österreich - Marschik, Matthias (Turia und Kant, 2008)
The intention of the book is to reduce the enormous Austrian research deficiency concerning the reappraisal of the sporting life during the NS-era. Therefore it will depict all sportive areas on the "Austrian" territory between March 1938 and April 1945, including top sports and sports for all, mass and monority sports, sports in clubs, youth sports and also sports practices of the formations of the NSDAP. Due to the enormous quantity of material, this overview will be contrasted by a precise analysis of three specific periods: the months after the "Anschluss", the autumn 1939 and the period after Stalingrad. It can be shown, that and how the regime dictated the basic conditions of sports, but there can also be found some grey area, in which those who were involved found resp. created freedom by strategies of mutual adaption. This freedom was used by different groups in specific ways: by the regime to calm down the working class or to soothe anti-prussian resentments, by the athletes to get some privileges and by the spectators to keep a glimpse of good luck. Not instrumentalization defined sports, but a negotiation of interests. It is just gaze on the everyday life of sports and the inherent permanent negotioations between regime and the people, that refer to the book´s contribution to the long term discussion on national socialism, which exceeds the field of sports: The political and cultural system of the Nazi-era could not be understood by looking at power, competences or possibilities of the regime in comparison with the people´s experiences and feelings of subjection, from which historical sciences construct the image of an interlude, which cannot be included in the evolutionary development of modernity. Looking on sports not only claryfies, to which extent cultural traditions led on and how "normality" was kept alive, but shows, in which ways changes and new valuations were obviously shared and use by the people. This concerned changing definitions of the sense of community, of gender, youth, work and performance. The special importance of sports can be found in substantiating these articulations by giving them authenticity and tracing them back to the nature of men. The analysis of sporting life in the NS-era may serve as an cause for questioning the contemporarygaze on the Nazi state. For all people, who were allowed to be included, life in national socialism offered - in spite of holocaust and World War - supply of a pleasant, self-detemined and enjoyable livehood. Who leaves aside or overlooks this facet of the Nazi dictatorship, will not be able to understand the acceptance and fascination of the regime and evoke just this often senseless metaphors of refusal, which mostly shape actual discourses.